Microalgae Production Tetraselmis sp., Thalassiosira sp. and Porphyridium sp. with a Combination of EMS & UV-C Mutations Based on Biomass and Lipid Content per Liter of Culture - Elida Purba; Iksan (Jurnal Teknologi dan Inovasi Industri (JTII), 2025)
This study aims to determine the effect of giving both aspects, namely, EMS mutagen and UV-C light on microalgae Tetraselmis sp., Thalassiosira sp ., and Porphyridium sp. so that the comparison can be known on biomass and lipid productivity. Both EMS and UV-C mutagen treatments were applied to wild-type and mutated microalgae. Culturing was carried out for 7 days in a photobioreactor with a capacity of 8L. The treatment of mutated microalgae was added with 0.5 M EMS and UV-C irradiation for 3 min. Cell density was calculated from day 1 to 7 in each type of microalgae using a haemocytometer. The results showed that mutagens caused a decrease in cell density in Tetraselmis sp., Thalassiosira sp., and Porphyridium sp. by 37%, 50%, and 2%, respectively, from the wild type. The biomass results showed that mutagens caused a decrease in microalgae Tetraselmis sp. and Porphyridium sp. by 21% and 13%, but an increase in microalgae Thalassiosira sp. by 4% from the wild type. Mutagens also affect the lipid content of microalgae because they significantly increase the lipid content of mutated microalgae Tetraselmis sp., Thalassiosira sp., and Porphyridium sp. by 20.54%, 11.20%, and 20.39%, respectively.